Identifikasi Akuifer di Sekitar Kawasan Karst Gombong Selatan Kecamatan Buayan Kabupaten Kebumen dengan Metode Geolistrik Konfigurasi Schlumberger: Sinta Maemuna, D. Darsono, Budi Legowo - Sinta Maemuna Sinta Maemuna; Darsono Darsono; Budi Legowo Budi Legowo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
Karst is usually composed from limestone, which often leaks rain water through holes in the limestone. As the result, drought often happens during dry season. We conducted a study to identify aquifer using geo-electric method with Schlumberger configuration, around the Southern Gombong Karst Region in Buayan district, precisely in Nogoraji, Jogomulyo, and Jatiroto village.The obtained data were processed using IPI2win software, and then we made 2D model using RockWorks 15. From this model, we found that a shallow aquifer as sandstone is located at the depth of 7,57-23,8 m, and an aquifer as breccias at the depth of 144-242 m. Both aquifer are located in T4 (Jogomulyo). Additionally, we also found an aquifer as limestone at the depth of 131-223 m, which is located in T5 (Nogoraji). However, we did not found any aquifer in T1 (Jatiroto), T2 (Jogomulyo), and T3 (Jogomulyo), because we only identified marl, tuff, tuffaceous marl and clay layer, which are impermeable.